Scoping study brief - State of index-based crop insurance services in East Africa - Osumba, Joab J.L.; Recha, John W.M. (2019)
This brief presents the findings of a scoping study on index-based crop insurance in East Africa, conducted as a requirement for the Climate Resilient Agribusiness for Tomorrow (CRAFT) Project, under Work Stream 3 on Enabling Environment for Climate-Smart Agriculture (CSA). The broad objective was to identify potential for index-based crop insurance, and gaps and barriers to roll-out in the current enabling environment for Kenya, Tanzania and Uganda, in order to inform the development of CRAFT’s policy influencing and advocacy strategy. It was also meant to identify options to support the creation of an enabling policy environment that is more conducive to engagements and investments in index-based crop insurance.